Analisis Strategi Pemasaran UMKM untuk Meningkatkan Pertumbuhan Bisnis di Era Digital: Strategic Analysis of MSMEs for the Advancement of Digital Age Business - Birgithri, Andzelika; Syafira, Tasya; Louise, Natalia (Technomedia Journal, 2024)
The global market has experienced a significant transformation along with the development of digital business technology, especially Micro, Small and Medium Enterprises (MSMEs) which are faced with new challenges in utilizing the digital era to increase product growth. This research aims to investigate effective marketing strategies in accelerating business growth in the digital era. MSMEs often face difficulties in adapting to these changes and exploiting them optimally for their growth. Despite the enormous opportunities offered by digital technology, many MSMEs have still not adopted the right marketing strategies to achieve success in the digital era. This causes many MSMEs to be trapped in intense competition or even lose their market share. This research aims to explore effective marketing strategies in increasing business growth in the digital era and to provide practical guidance for MSMEs in implementing these strategies. This research uses a qualitative approach by conducting case studies of several MSMEs that have successfully implemented digital marketing strategies. Data was collected through in-depth interviews and documentation analysis. The research results show that an effective digital marketing strategy includes the use of social media, relevant and interesting content, search engine optimization (SEO), and data analysis for better decision making. Implementing the right digital marketing strategy can significantly increase MSME business growth in the digital era. It is important for MSMEs to continue to develop knowledge and skills in this regard to remain relevant and competitive in this increasingly changing market.